Derek Jarman : A Biography - Peake, Tony (Book collections on Project MUSE., 2011)
England's most controversial filmmaker and director, Derek Jarman was also a gifted writer, artist, gardener, designer, and an outspoken AIDS and queer rights activist. Jarman's story stretches from his childhood in postwar Britain to art school days at the Slade School of Art and the making of many acclaimed films, including Sebastiane, Jubilee, Caravaggio, and Blue. A chronicle of sexual fear and repression, the devastation of disease, and inimitable courage and grace, Derek Jarman: A Biography is an honest and brilliant tribute to the uncompromising life and art of Derek Jarman.